The shoulder ([St. Louis, MO] : Mosby-Year Book, 1994)
Succesful athletic trainers, physical therapists, physicians and other allied health students and professionals must master injury evaluation techniques and tests. This video series features step by step instructions on how to evaluate sports injuries by demonstrating the following basic assesment tests: bone integrity,muscular function and range of motion, joint ligamentatous stability, neurological dysfunction, joint derangement and effusion, inflammantory conditions.
Keywords: Shoulder -- injuries -- videocassettes; Athletic Injuries -- diagnosis -- videocassettes; Physical Examination -- methods -- videocassettes